2021
DOI: 10.3390/cancers13051179
|View full text |Cite
|
Sign up to set email alerts
|

Conversion Therapy of Intrahepatic Cholangiocarcinoma Is Associated with Improved Prognosis and Verified by a Case of Patient-Derived Organoid

Abstract: This study was performed to determine the efficacy of conversion therapy in intrahepatic cholangiocarcinoma (IHCC) and explore the feasibility of cancer organoid to direct the conversion therapy of IHCC. Patient data were retrospectively reviewed in this study and cancer organoids were established using tissues obtained from two patients. A total of 42 patients with IHCC received conversion therapy, 9 of whom were downstaged successfully, and another 157 patients were initially resectable. Kaplan–Meier curves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Ganesh et al also reported that cancer PDO of rectal cancer can predict the sensitivity of original cancer to both chemotherapy and radiotherapy [ 15 ]. Recently, our team has successfully established PDOs of intrahepatic cholangiocarcinoma (iCCA) and evaluated its drug sensitivity, which was consistent with the observed clinical effects [ 16 ]. However, very few studies have established PDO from eBTC to date.…”
Section: Introductionmentioning
confidence: 88%
“…Ganesh et al also reported that cancer PDO of rectal cancer can predict the sensitivity of original cancer to both chemotherapy and radiotherapy [ 15 ]. Recently, our team has successfully established PDOs of intrahepatic cholangiocarcinoma (iCCA) and evaluated its drug sensitivity, which was consistent with the observed clinical effects [ 16 ]. However, very few studies have established PDO from eBTC to date.…”
Section: Introductionmentioning
confidence: 88%
“…Although tumor origin, carcinogenesis, and response to chemotherapy are expected to differ between the two types, in-depth studies of these differences have proven experimentally problematic owing to the absence of applicable ex vivo subtype models and difficulties in acquiring sufficient tumor tissue for analysis. Therefore, a truly representative model of cholangiocarcinoma subtypes is needed for studying differences in development, carcinogenesis, and anticancer drug responsiveness between types.Recently developed organoid culture techniques enable the formation of adult stem cell-derived cancer organoids from cholangiocarcinoma specimens [15][16][17][18][19][20] . Importantly, the resulting organoids show similar phenotypic and genetic characteristics compared with the original primary tumor.…”
mentioning
confidence: 99%
“…( 51 ) reported that 22% of patients with advanced ICC receiving radioembolization plus chemotherapy could be downstaged to surgical intervention, of which 8 patients survived after 24 months of follow-up. By means of systemic or regional therapy, adequate tumor downstaging was accomplished, and patients could obtain a generally favorable prognosis ( 52 54 ). Le Roy B. et al.…”
Section: Discussionmentioning
confidence: 99%